A Case for a Polyphonic Anthropology: Giving Voice to Experiences of Women of Color - SimonMary Asese Aihiokhai (Religions, 2022)
Discourses in theological anthropology ought to begin by centering the human condition in all its multiple expressions. Experiences of marginalized women of color do not always make it to the forefront of such discourses. What does it mean to be a woman of color in God’s imagination? How can we speak of the human person as a rainbow reality of diverse narratives and experiences? This work attempts to address these questions by appropriating a critical hermeneutic that allows for a polyphonic discourse on what it means to be human. In doing this, this work articulates arguments for a polyphonic anthropology. It critiques the traditional understanding of human as imago Dei. It opens up a new horizon for conceiving of the human person through the multiple experiences of humans, especially women of color, who, traditionally, have not always been acknowledged to be truly human in a world defined by narratives of erasure.